Quraysh Commercial Dominance: Political and Security Strategies on the Arabian North–South Trade Route - Apipudin Apipudin; Tarasyah Fazlin (Hasanuddin University, 2026)
This article critically analyzes the commercial hegemony of the Quraysh tribe over the Yemen–Levant trade routes during the pre-Islamic era. Moving beyond descriptive narratives, this study employs an economic history approach and socio-political analysis, integrated with critical source evaluation of Islamic historiographical traditions, to examine Quraysh dominance. The focus includes the institutionalization of ilaf diplomacy, the Ahabish military alliance, and the capitalization of the Ka‘bah’s sacred status (haram). Findings indicate that Quraysh success was not merely geographical, but a synthesis of structured mercantile networks, strategic maneuvering, and spiritual legitimacy. This trade dominance transformed Mecca into a cosmopolitan hub and fostered regional integration. The study concludes that Quraysh commercial hegemony provided the vital socio-economic and logistical infrastructure for the subsequent emergence and expansion of Islam. Keywords: Quraysh; Pre-Islamic Trade; Yemen–Levant Route; Ilaf Diplomacy; Economic Hegemony.